The effect of high frequency electric field on enhancement of chondrogenesis in human adipose-derived stem cells - Esfandiari, Ebrahim (Iran J Basic Med Sci, 2014)
OBJECTIVE(S): Osteoarthritis (OA) is globally one of the most common diseases from the middle age onwards. Cartilage is an avascular tissue therefore it cannot be repaired in the body. Conservative treatments have failed as a good remedy and cell therapy as a decisive cure is needed. One of the best and easily accessible cell sources for this purpose is adipose-derived stem cells which can be differentiated into chondrocytes by tissue engineering techniques. Chemical and physical inducers have a key role in stem cell - chondrocyte differentiation. We have tried to determine the role of electric fields (EF) in promoting this kind of chondrogenesis process. MATERIALS AND METHODS: Human adipose derived stem cells (ADSCs) were extracted from subcutaneous abdominal adipose tissue during cesarean section. A high frequency (60 KHz) EF (20 mv/cm), as a physical inducer for chondrogenesis in a 3D micromass culture system of ADSCs was utilized. Also, MTT, ELISA, flow cytometry, and real-time PCR techniques were used for this study. RESULTS: We found that using physical electric fields leads to chondrogenesis. Furthermore, results show that using both physical (EF) and chemical (TGFβ3) inducers simultaneously, has best outcomes in chondrogenesis, and expression of SOX(9) and type II collagen genes. It also causes significant decreased expression of type I and X collagen genes in pure EF group compared with control group. CONCLUSION: The EF was found as a proper effective inducer in chondrogenic differentiation of human ADSCs micromass culture.